2016
DOI: 10.1002/2015jd024173
|View full text |Cite
|
Sign up to set email alerts
|

WACCM‐D—Improved modeling of nitric acid and active chlorine during energetic particle precipitation

Abstract: Key points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
81
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(94 citation statements)
references
References 47 publications
13
81
0
Order By: Relevance
“…In the SH, the daily-varying enhancements also occur when the HNO 3 abundance is increasing as the winter approaches, while it is decreasing in the NH (see Figure 1). Figure 2 (right), we note that the HNO 3 increase due to the April 2010 EEP event in WACCM-D is much smaller than the corresponding increase after the January 2005 SPE, discussed by Andersson et al (2016). They found an increase in HNO 3 of 0.5-1.0 ppb near 70-75 km during the SPE (their Figure 9, top) in the NH.…”
Section: Monthly Mean Polar-averaged Distributions Of Ion Clustersmentioning
confidence: 71%
See 1 more Smart Citation
“…In the SH, the daily-varying enhancements also occur when the HNO 3 abundance is increasing as the winter approaches, while it is decreasing in the NH (see Figure 1). Figure 2 (right), we note that the HNO 3 increase due to the April 2010 EEP event in WACCM-D is much smaller than the corresponding increase after the January 2005 SPE, discussed by Andersson et al (2016). They found an increase in HNO 3 of 0.5-1.0 ppb near 70-75 km during the SPE (their Figure 9, top) in the NH.…”
Section: Monthly Mean Polar-averaged Distributions Of Ion Clustersmentioning
confidence: 71%
“…This variant of WACCM called WACCM-D, where D stands for the D-layer of the ionosphere (below the mesopause), is described in detail by Verronen et al (2016). Andersson et al (2016) investigated the chemical effects of the SPE of 2005, in particular on HNO 3 , and showed that the production of HNO 3 increased by 2 orders of magnitude between 40 and 70 km, bringing WACCM-D closer to the MLS satellite observations. The aim of this paper is to investigate, through a case study, the effect of EEP events on the distribution of HNO 3 and relevant ion clusters in the new WACCM-D model in comparison to the standard WACCM, in the presence of medium-to-high energy electron (MEE) forcing.…”
Section: Introductionmentioning
confidence: 99%
“…For a comprehensive description of WACCM-D and its lower ionospheric performance, see Verronen et al (2016). Andersson et al (2016) showed that the addition of D region ion chemistry into WACCM significantly improves modeling of polar HNO 3 , HCl, ClO, OH, and NO x and that WACCM-D can model atmospheric effects of the January 2005 SPE (event 58 in this study, max 5,040 pfu) as compared to Aura/MLS observations. SD-WACCM-D (WACCM4) was run for the time periods of the 62 SPEs examined in this study with preconfigured specified dynamics driven by MERRA 19 × 2 (Rienecker et al, 2011) meteorological fields for the year 2000 with a 6-hr time resolution.…”
Section: Modelingmentioning
confidence: 99%
“…The SIC model chemical scheme includes 70 ions, of which 41 are positive and 29 negative, and 34 neutral species with simple vertical transport (molecular and eddy diffusion). WACCM‐D (Verronen et al, ) includes a D ‐region ion scheme of 307 reactions of 20 positive ions and 21 negative ions, allowing the 3‐D global model to account for substantial HNO 3 enhancements observed in the mesosphere at altitudes ~50–80 km after major SPEs (Andersson et al, ). WACCM‐SIC (Kovács et al, ) includes a more complete set of ion‐neutral reactions from the detailed D ‐region ion chemistry in the SIC model, while ion‐ion recombination reactions are included for three major positive ions (NO + , H + (H 2 O) 3 , and H + (H 2 O) 4 ) and three major negative ions (O 2 − , CO 3 − , and NO 3 − ).…”
Section: Introductionmentioning
confidence: 99%